Mechanical sciences-2 : thermodynamics and fluid mechanics - Ghosh, Bankim Bihari (Vikas, 2009)
Mechanical sciences-2 : thermodynamics and fluid mechanics / Ghosh, Bankim Bihari. -- New Delhi: Vikas, 2009 620.1 G427e2 2nd ed No. of Copies : 1